Mechanisms driving the global tropical response to a weakened AMOC during Heinrich Stadial 1 - A.E. Lawman; C. Sun; X. Wu; T. Sun; N. Piatrunia; K. Gomez; M. Kageyama; U. Merkel; M. Prange; B. Otto-Bliesner; X. Zhang; P. DiNezio; et al. (Quaternary Science Reviews, 2025)

A culture-independent study of the structure, functions and methane oxidation activity of microbial communities of geothermal springs in Dagestan - A. I. Slobodkin; I. I. Rusanov; G. B. Slobodkina; N. A. Chernyh; A. R. Stroeva; A. Y. Merkel (Extremophiles, 2025)

Taxonomic and metabolic diversity of microbial communities in a thermal water stream in Uzbekistan and proposal of two new classes of uncultivated bacteria, Desulfocorpusculia class. nov. and Tepidihabitantia class. nov., named following the rules of SeqCode - Galina B. Slobodkina; Alexander Y. Merkel; Kseniya V. Kondrasheva; Alexandra R. Stroeva; Elizaveta A. Bonch-Osmolovskaya; Kahramon D. Davranov; Alexander I. Slobodkin (Systematic and Applied Microbiology, 2025)

A new type of submarine chimneys built of halite - C. Siebert; D. Ionescu; U. Mallast; S. Merchel; B. Merkel; P. Möller; S. Pavetich; T. Pohl; T. Rödiger; Y. Yechieli (Science of The Total Environment, 2024)

Potential biosignatures in goethite deposits in Mavros Vrachos Quarry hypogene cave - G. Lazaridis; D. Bessas; M. Panou; B. Maróti; W. Crichton; V. Melfos; L. Papadopoulou; S. Gkelis; D.G. Merkel; A.I. Chumakov; P. Voudouris (CATENA, 2024)

Pythium insidiosum: insights into biofilm formation and antibiofilm activity of antifungal drugs - B. Pippi; E. S. Loreto; S. Merkel; A. R. Joaquim; M. E. Krummenauer; P. Reginatto; M. H. Vainstein; S. F. Andrade; A. M. Fuentefria; J. M. Santurio; R. A. Zanette (Brazilian Journal of Microbiology, 2023)

Moorella sulfitireducens sp. nov., a thermophilic anaerobic bacterium isolated from a terrestrial thermal spring - Galina B. Slobodkina; A. Y. Merkel; A. A. Kuchierskaya; A. I. Slobodkin (Extremophiles, 2022)

Pelomicrobium methylotrophicum gen. nov., sp. nov. a moderately thermophilic, facultatively anaerobic, lithoautotrophic and methylotrophic bacterium isolated from a terrestrial mud volcano - G. B. Slobodkina; A. Y. Merkel; A. A. Novikov; E. A. Bonch-Osmolovskaya; A. I. Slobodkin (Extremophiles, 2020)

Circumpolar dynamics of a marine top‐predator track ocean warming rates - Sébastien Descamps; Tycho Anker‐Nilssen; Robert T. Barrett; David B. Irons; Flemming Merkel; Gregory J. Robertson; Nigel G. Yoccoz; Mark L. Mallory; William A. Montevecchi; David Boertmann; Yuri Artukhin; Signe Christensen‐Dalsgaard; et al. (Global Change Biology, 2017)
Global warming is a nonlinear process, and temperature may increase in a stepwise manner. Periods of abrupt warming can trigger persistent changes in the state of ecosystems, also called regime shifts. The responses of organisms to abrupt warming and associated regime shifts can be unlike responses to periods of slow or moderate change. Understanding of nonlinearity in the biological responses to climate warming is needed to assess the consequences of ongoing climate change. Here, we demonstrate that the population dynamics of a long‐lived, wide‐ranging marine predator are associated with changes in the rate of ocean warming. Data from 556 colonies of black‐legged kittiwakes Rissa tridactyla distributed throughout its breeding range revealed that an abrupt warming of sea‐surface temperature in the 1990s coincided with steep kittiwake population decline. Periods of moderate warming in sea temperatures did not seem to affect kittiwake dynamics. The rapid warming observed in the 1990s may have driven large‐scale, circumpolar marine ecosystem shifts that strongly affected kittiwakes through bottom‐up effects. Our study sheds light on the nonlinear response of a circumpolar seabird to large‐scale changes in oceanographic conditions and indicates that marine top predators may be more sensitive to the rate of ocean warming rather than to warming itself.

Microbial diversity and autotrophic activity in Kamchatka hot springs - Alexander Yu. Merkel; Nikolay V. Pimenov; Igor I. Rusanov; Alexander I. Slobodkin; Galina B. Slobodkina; Ivan Yu. Tarnovetckii; Evgeny N. Frolov; Arseny V. Dubin; Anna A. Perevalova; Elizaveta A. Bonch-Osmolovskaya (Extremophiles, 2017)

Potential misidentifications of two climate indicator species of the marine arctic ecosystem: Calanus glacialis and C. finmarchicus - T. M. Gabrielsen; B. Merkel; J. E. Søreide; E. Johansson-Karlsson; A. Bailey; D. Vogedes; H. Nygård; Ø. Varpe; J. Berge (Polar Biology, 2012)

Low‐cost aerial photography for high‐resolution mapping of hydrothermal areas in Yellowstone National Park - B. Planer‐Friedrich; J. Becker; B. Brimer; B. J. Merkel (International Journal of Remote Sensing, 2008)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Environmental Impact by Spill of Geothermal Fluids at the Geothermal Field of Los Azufres, Michoacán, Mexico - P. Birkle; B. Merkel (Water, Air, & Soil Pollution, 2000)

Reactive transport modeling of uranium 238 and radium 226 in groundwater of the Königstein uranium mine, Germany - O. Nitzsche; B. Merkel (Hydrogeology Journal, 1999)

The influence of municipal waste on uranium mill tailings: A hydrogeochemical study on a mixed tailings site - C. Helling; O. Nitzsche; B. Ullrich; B. Merkel (Mine Water and the Environment, 1998)